HUBUNGAN ANEMIA DAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH (BBLR) DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Istiani, Istiani; Erika, Erika; Awaluddin, Awaluddin (Ensiklopedia of Journal, 2025)
Abstract: According to the World Health Organization (WHO), in 2023, the global LBW rate will be about 15.5% or equivalent to 20 million babies born each year, about 96.5% of LBW occurs in developing countries, which is a health problem and very influential in the long term. There are several factors that can cause LBW, including lack of nutrition during pregnancy and anemia. The purpose of this study was to determine the relationship between Chronic Energy Deficiency (CED) and anemia on the incidence of LBW in RSUD Arifin Achmad Riau Province. The design of this study is correlation with retrospective approach. The population in this study amounted to 145 respondents data obtained from the medical records of Arifin Achmad Hospital Riau Province using total sampling method. Data were collected using a questionnaire consisting of respondent characteristics (age, parity, gestational age, HB level, mother's age, education). Data analysis in this study used chi-square test with Pearson chi-square rule. The results of the study showed a relationship between anemia and chronic energy deficiency (CED) to the incidence of LBW in RSUD Arifin Achmad Riau Province with statistical test results p-value = 0.000 in each variable. The researcher's proposal to Arifin Achmad Hospital Riau Province is expected to know the factors that cause anemia and CED on the incidence of LBW.Keywords: Anemia, Chronic Energy Deficiency (CED), LBW